2002
DOI: 10.1111/1469-7610.00050
|View full text |Cite
|
Sign up to set email alerts
|

The development of impulsivity, fearfulness, and helpfulness during childhood: patterns of consistency and change in the trajectories of boys and girls

Abstract: We found that behavioural consistency over middle childhood varied across trajectory groups and across dimensions, and we identified sex differences in the distribution of children in the different trajectory groups that may reflect gender-specific risks for psychopathology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
108
0
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 190 publications
(128 citation statements)
references
References 60 publications
17
108
0
3
Order By: Relevance
“…This is an interesting finding given the historical tendency for boys to display more impulsivity than girls, both in normal (Cote, Tremblay, Nagin, Zoccolillo, & Vitaro, 2002) and Attention Deficit Hyperactivity Disorder (Newcorn et al, 2001) populations. The only other significant gender difference to emerge in terms of individual maladaptive behaviors in our study suggested that boys with SMS engage in more repetitive shouting than girls.…”
Section: Discussionmentioning
confidence: 69%
“…This is an interesting finding given the historical tendency for boys to display more impulsivity than girls, both in normal (Cote, Tremblay, Nagin, Zoccolillo, & Vitaro, 2002) and Attention Deficit Hyperactivity Disorder (Newcorn et al, 2001) populations. The only other significant gender difference to emerge in terms of individual maladaptive behaviors in our study suggested that boys with SMS engage in more repetitive shouting than girls.…”
Section: Discussionmentioning
confidence: 69%
“…Differences in approach-withdrawal behavior, suggesting elevated fear, shyness, and withdrawal in females, and greater high-intensity pleasure seeking in males, have also been documented during infancy and early toddlerhood (Carey & McDevitt, 1978;Gartstein & Rothbart, 2003;Martin, Wisenbaker, Baker, & Huttunen, 1997; Maziade, Broudreault, Thivierge, Caperaa, & Cote, 1984;Reznick, Gibbons, Johnson, & McDonough, 1989). These sex differences persist throughout childhood (Eaton & Enns, 1986;Cote, Tremblay, Nagin, Zoccolillo, & Vitaro, 2002). Other sex differences have been observed at older ages.…”
Section: Gender Differences In Temperamentmentioning
confidence: 80%
“…[41,200] However, a pattern of negative association between social anxiety and conduct problems is broadly consistent with other findings linking overall levels of fearlessness to high risk for conduct disorder. [201,202] Longitudinal outcome. Data on the course of SAD probably provide the most important information speaking to the validity of the SAD diagnosis in childhood, as they test the hypothesis that children with SAD face a high risk for becoming adults with SAD.…”
Section: Developmental Issuesmentioning
confidence: 99%